Devaluations, Deposit Dollarization, and Household Heterogeneity - Ferrante, Francesco; Gornemann, Nils (Review of Economic Studies, 2025)
Abstract We study the aggregate and redistributive effects of currency devaluations in a small open economy model with leverage-constrained banks and heterogeneous households. Our framework captures three stylized facts about financial dollarization in emerging economies: (1) a sizable share of domestic deposits is denominated in foreign currency; (2) these deposits represent significant foreign currency liabilities for local banks; and (3) dollar deposits are mainly held by wealthier households. A devaluation increases the real burden of foreign currency debt, causing an erosion of banks’ net worth, which depresses credit supply and economic activity. While richer households are partially insulated through their dollar deposits, poorer households cut consumption sharply in response to rising borrowing costs and falling real labor income. In our model deposit, dollarization amplifies the contractionary effects of a devaluation on output, investment, and consumption, in line with new empirical evidence for emerging economies. To achieve this result, both constrained intermediaries and heterogeneous households are crucial. In our framework, regulating dollarization can result in widespread welfare gains, especially for poorer households.